Legal Analysis of the Application of the Prudential Principle in the Safe Deposit Box Agreement between the Bank and the Customer - Mariska Fitriliya; Dudung Hidayat; Jaenudin Umar (Interdisciplinary Journal of Advanced Research and Innovation, 2026)
The banking industry plays a strategic role in Indonesia's economy, and banks are legally obligated to apply the prudential principle in all their business activities, including Safe Deposit Box (SDB) services. However, a legal gap exists between this obligation and the practice of using unilateral exemption clauses in standard SDB agreements, which potentially harms customers and creates legal uncertainty . The research problem focuses on the research of legal provisions governing SDB as well as the implementation of the principle of prudence in the relevant agreements. The purpose of this research is to analyze the regulations and the strengthening of the application of the principle of prudence in order to ensure legal certainty for customers. The method employed was normative juridical, based on the theory of Soerjono Soekanto and Sri Mamudji, primarily using secondary data supported by limited empirical data obtained through interviews. The research findings indicate that the use of standard SDB agreement clauses by banks clearly violates Article 18 Paragraph (1) letter a of the Consumer Protection Law, Rendering such clauses null and void by operation of law. In practice, weaknesses persist in the application of this principle, particulary concerning the use of clauses that exempt banks from liability to customers. Although banks implement layered security Standard Operating Procedures (SOP) base on the principle of prudence, they may still be held legally accountable if proven negligent in maintaining the SDB security system.